TINGKAT KEANDALAN UTILITAS KELISTRIKAN BANGUNAN GEDUNG BERTINGKAT DI KOTA SEMARANG - - Suyono; M. Tony Prasetyo; Luqman Assafat (MEDIA ELEKTRIKA, 2011)
Utility Electricity of building is one important component in supporting thefunction of the building. Electricity utility of a building must be safe, because the use of electrical energy in buildings is harmful to human and environmental uses. Thus, in the use of electrical energy and electrical utilities in a building must comply with regulations and meet specified minimum standards. Semarang as major cities in Indonesia have many buildings with a variety of functions. These buildings should provide a sense of security and comfort for the user and the environment against the use of electrical utilities. It is necessary for assessing the levelof reliability of the electrical utility-rise buildings in the city of Semarang.Using qualitative methods by scoring and quantitative method by measuring electrical quantities of a number of samples, the high rise buildings in the city of Semarang on average have a higher utility electricity of buildings with less reliable category.Keywords: level of reliability, utility electricity of buildings, Semarang city